2012
DOI: 10.1111/j.1743-6109.2012.02764.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of a New Self-Help Booklet for Premature Ejaculation

Abstract: Introduction.  Premature ejaculation (PE) is quite common. Although effective treatments do exist, only a few affected people consult a practitioner in order to overcome their problem. At the same time, studies have shown that reading didactical documents about their PE problem (bibliotherapy) can be useful to men. Aim.  The aim of this study was to improve the bibliotherapy approach using up‐to‐date knowledge and techniques. The expected benefits were the following: (i) an effective manual shorter than previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
0
6
0
7
Order By: Relevance
“…Yet at least three clinical trials appear to have refuted this proposal. Thus, De Carufel and Trudel (2006), De Sutter et al (2002), and Kempeneers et al (2012) found that subjects affected by particularly short ejaculation latency may also respond favourably to sexual behavioural therapy. It is true they showed less improvement in comparison to PE subjects with penetration duration exceeding one minute (Kempeneers et al, 2012), but there were improvements nonetheless.…”
Section: Should Primary Severe Pe Be Considered a Neurobiological Dismentioning
confidence: 96%
See 1 more Smart Citation
“…Yet at least three clinical trials appear to have refuted this proposal. Thus, De Carufel and Trudel (2006), De Sutter et al (2002), and Kempeneers et al (2012) found that subjects affected by particularly short ejaculation latency may also respond favourably to sexual behavioural therapy. It is true they showed less improvement in comparison to PE subjects with penetration duration exceeding one minute (Kempeneers et al, 2012), but there were improvements nonetheless.…”
Section: Should Primary Severe Pe Be Considered a Neurobiological Dismentioning
confidence: 96%
“…Thus, De Carufel and Trudel (2006), De Sutter et al (2002), and Kempeneers et al (2012) found that subjects affected by particularly short ejaculation latency may also respond favourably to sexual behavioural therapy. It is true they showed less improvement in comparison to PE subjects with penetration duration exceeding one minute (Kempeneers et al, 2012), but there were improvements nonetheless. Similar findings were obtained for medication treatments (Waldinger, 2007), such that at the end of the day, latencies shorter than one minute represent a severity gradient of the disorder that limits, not to say eradicates, the effectiveness of any treatment whatsoever.…”
Section: Should Primary Severe Pe Be Considered a Neurobiological Dismentioning
confidence: 96%
“…Au moins trois essais cliniques semblent pourtant démentir le propos. De Carufel et Trudel (2006), De Sutter et al (2002) et Kempeneers et al (2012) ont en effet trouvé que des sujets affectés d'une latence éjaculatoire particulièrement courte pouvaient également répondre favorablement à un traitement sexo-comportemental. Les améliorations sont, il est vrai chez eux de moindre ampleur qu'elles ne le sont chez les sujets EP signalant a priori des durées de pénétration supé-rieures à une minute (Kempeneers et al, 2012), mais elles n'en sont pas moins présentes.…”
Section: Faire De L'ep Primaire Sévère Un Trouble Neurobiologique : Punclassified
“…De Carufel et Trudel (2006), De Sutter et al (2002) et Kempeneers et al (2012) ont en effet trouvé que des sujets affectés d'une latence éjaculatoire particulièrement courte pouvaient également répondre favorablement à un traitement sexo-comportemental. Les améliorations sont, il est vrai chez eux de moindre ampleur qu'elles ne le sont chez les sujets EP signalant a priori des durées de pénétration supé-rieures à une minute (Kempeneers et al, 2012), mais elles n'en sont pas moins présentes. Du reste un constat similaire vaut également pour les traitements médicamenteux (Waldinger, 2007) de sorte qu'il apparaît au bout du compte que les latences inférieures à une minute reflètent un gradient de sévérité de l'affection, lequel limite, sans pour autant l'anéantir, l'efficacité des traitements quels qu'ils soient.…”
Section: Faire De L'ep Primaire Sévère Un Trouble Neurobiologique : Punclassified
See 1 more Smart Citation